The influence of skin tears following collagenase treatment of Dupuytren's disease on treatment outcomes. (May 2021) - Phan, Robert; Rozen, Warren M.; Dela Cruz, Giselle; Tobin, Vicky; Hunter-Smith, David J.
This study investigated influence of skin tears on patient-reported outcomes of injection of collagenase clostridium histolyticum for Dupuytren's disease and association between extension deficit of digits before injection and skin tear after the injection. From 2016 to 2018, 391 Dupuytren's cords were treated in 184 patients in a prospective cohort study and the patients were evaluated before injection and six months after injection. Skin tears occurred in 50% of these patients. We found no significant differences in the patient-reported outcomes between patients with or without skin tears. A higher extension deficit before treatment was associated with significantly increased frequency of skin tears. We conclude that the incidence of skin tears after injection does not affect patient reported outcomes six months after collagenase injection, but the incidence of skin tears is significantly associated with the severity of pre-treatment finger extension deficits. Level of evidence: II